Impact of the cooling system on the costs of electrical demand of a federal public university - case study of the Federal University of Espírito Santo - Benedito, Vinícius Molini; Moreira, Kelly Costa Cabral Salazar Ramos; Viana, Thiago Maciel; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2020)
The energy crisis, the imminence of electric power shortages and budget cuts are major threats to the functioning of several Brazilian public universities. Conservation and conscious use of electrical energy can be achieved through relatively simple actions, which do not alter the standard of comfort and routine functions. Almost half of the traditional electricity consumption of a public building is related to air conditioning systems, the study was based on data on electrical consumption and climatic information extracted from the temperature history observed in the UFES region. With such information, it was possible to determine the impact of the use of refrigeration devices on the total cost of the electrical energy consumed and to propose regulatory measures and the adoption of new refrigeration systems, in order to guarantee greater energy efficiency. The proposed model suggests a 35.47% reduction in energy consumption.
Keywords: Public management; Energy efficiency; Universities; Costs